2019
DOI: 10.26434/chemrxiv.8246840.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

“Hydrotriphylites” Li1-xFe1+x(PO4)1-y(OH)4y as Cathode Materials for Li-ion Batteries

Abstract: Lithium iron phosphate LiFePO<sub>4</sub> triphylite is now one of the core positive electrode (cathode) materials enabling the Li-ion battery technology for stationary energy storage applications, which are important for broad implementation of the renewable energy sources. Despite the apparent simplicity of its crystal structure and chemical composition, LiFePO<sub>4</sub> is prone to off-stoichiometry and demonstrates rich defect chemistry owing to variations in the cation content an… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…In that case, Fe excess and/or Li/ Fe antisite defects can be formed due to kinetic limitation of the reaction. 6,14,29 In contrast, the Li 3 PO 4 -based route is known to produce high-performance lithium iron phosphate free from Fe + Li defects. 30−34 It is obvious that insertion of Li + into the Fe position M2 of the LiFePO 4 crystal structure should result in partial oxidation of the Fe cations up to +3 state in order to maintain the charge balance.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In that case, Fe excess and/or Li/ Fe antisite defects can be formed due to kinetic limitation of the reaction. 6,14,29 In contrast, the Li 3 PO 4 -based route is known to produce high-performance lithium iron phosphate free from Fe + Li defects. 30−34 It is obvious that insertion of Li + into the Fe position M2 of the LiFePO 4 crystal structure should result in partial oxidation of the Fe cations up to +3 state in order to maintain the charge balance.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The final stage of the reaction is chemical exchange of “0.5Fe” for 1Li. In that case, Fe excess and/or Li/Fe antisite defects can be formed due to kinetic limitation of the reaction. ,, In contrast, the Li 3 PO 4 -based route is known to produce high-performance lithium iron phosphate free from Fe + Li defects. …”
Section: Resultsmentioning
confidence: 99%
“…It should also be noted that LiFePO 4 demonstrates extremely rich defect chemistry including Li/Fe antisite mixing, partial Li for Fe or Fe for Li substitution, partial Fe oxidation, cation vacancies, substitution of phosphate with hydroxyl groups etc. which add an extra complexity to the problem dramatically altering the electrochemical behavior (for instance, suppressing phase separation) . Obviously, the understanding of the complex interplay of the intercalation rate‐controlling factors requires accurate experimental characterization of intercalation kinetics and quantitative estimation of the key kinetic parameters.…”
Section: Introductionmentioning
confidence: 99%
“…The P-deficient LiFePO 4 was synthesized via a hydrothermal route at a low concentration of initial reagents . The prepared solutions of 7 LiOH (0.0075 mol, NCCP, 98%) and H 3 PO 4 (0.0025 mol, Reakhim, 98%) in D 2 O (Kurchatov Institute, 99.8%) were first mixed to form a Li 3 PO 4 precipitate.…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, infrared spectroscopy showed absorption bands characteristic of the structural OH bonds, while thermogravimetric/mass spectrometry analysis confirmed the water loss of the LFP sample in two stages with onsets at 350 and 450 °C, which are much higher compared to the typical temperatures of the adsorbed water loss. Additionally, the density functional theory (DFT) calculations showed that the formation of PO 4 /O 4 H n ( n = 1–4) defects is feasible under the synthesis conditions …”
Section: Introductionmentioning
confidence: 99%